The Early Nineteenth-Century Unitarian Campaign to change English Marriage Law - Wykes, David L. ca. 20./21. Jh. (Studies in church history, 2023)
The 1836 Marriage Act has received surprisingly little attention from historians of Dissent, despite its significance in permitting non-Anglicans to conduct legally recognized marriages according to their own ceremonies in Dissenting places of worship. The Clandestine Marriages Act (1753), better known as the Hardwicke Act, had limited valid marriages to the rites of the Church of England. Only Jews and Quakers were exempt. By the early nineteenth century the Anglican marriage service was objectionable to Unitarians because of the references to the Trinity. The struggle to change the Marriage Act was initiated by the Freethinking Christians, who engaged in a controversial and highly visible public protest during the marriage service. They successfully engaged the broader Unitarian movement in their campaign, who through the medium of the Unitarian Association undertook a remarkable, though largely fruitless, struggle to change the law until joined by the rest of Dissent in the early 1830s.